The Fourth International Workshop on Dynamic Scheduling Problems: Extended Abstracts - Gawiejnowicz, Stanisław (ed.) (Polish Mathematical Society, 2023)
This book contains extended abstracts of the plenary lecture and papers presented at the Fourth International Workshop on Dynamic Scheduling Problems, June 5th-6th, 2023, Winterthur, Switzerland.
Keywords: algorithms; approximation algorithms; competing agents; competitive analysis; data gathering networks; deteriorating jobs; due-dates; dynamic programming; dynamic scheduling; emergency department; fatigue effect; fl ow shop; FPTAS; healthcare; job rejection; just-in-time jobs; learning effect; lot scheduling; lot sizing; LP rounding; maintenance activities; makespan; monotone dynamic programming; NP-hardness; order rejection; parallel machines; position-dependent processing times; precedence constraints; proportionate flow shop; pseudo-polynomial time algorithms; PTAS; rate-modifying activities; robust optimization; robust scheduling; scenario-based planning-approach; scheduling; scheduling over scenarios; SFPTAS; shortening jobs; single machine; startup times; step-deteriorating processing times; stochastic scheduling; time complexity; total completion time; total load; total weighted completion time; variable communication speed